Estudos microgravimétricos da deposição de cobre sobre eletrodos de cromo passivado - Souza, Tatiana Barbosa Petroni Lima de (2002)
Recently were obtained in our laboratory results indicating that Cu deposition on Cr2O3 happens in two steps: at the first one, there is the deposition of an amount smaller than one Cu monolayer, and at the second one there is Cu bulk deposition. Evidences show that the first step mechanism is UPD like, although it is necessary a deeper investigation. In this work the electrochemical quartz crystal microbalance (EQCM) was employed to characterize such system, using two different electrolytes: H2SO4 and HClO4. The obtained results indicate that Cu deposition happens in a reversible way in H2SO4 at the potentials range studied, and ∆m(y) x ∆Q(x) curves analysis showed that faradaic processes predominate at the system, but anionic and H2O adsorption can also occur on the electrode. The kind of deposited or adsorbed species will depend on the applied potential. In the case of HClO4, microgravimetric studies show that the observed irreversibility to the Cu electrodeposition can be related to two factors: (1) coadsorption of Cl- ions coming from electrolyte degradation, what would catalyse and stabilize Cu deposition; or (2) irreversible NO3 - ions reduction (coming from the used precursor salt) after Cu deposition, taking into account the Cu catalytic activity to these ions reduction, and the extent of calculated molar mass values.